COMPARISON OF THE HYDROLOGICAL CHARACTERISTICS OF 3 SMALL EXPERIMENTAL HOLM OAK FORESTED CATCHMENTS IN NE SPAIN IN RELATION TO LARGER AREAS - Piñol, J; Avila, a; Escarre, A; LLEDO, M J; Rodà, F (VEGETATIO, 1992)
Precipitation and streamflow have been measured in three small (0.04-0.52 km2) experimental catchments covered by dense holm oak (Quercus ilex L.) forests. Two of them are in the Prades mountains and one in the Montseny mountains (NE Spain). Here we test the hydrological representativeness of these catchments against the streamflow record at two nearby larger (34-60 km2) catchments, one from each massif. Comparisons of (i) annual streamflow, (ii) seasonal distribution of streamflow, and (iii) flow duration curves were made. At Prades, for the period of common record, mean annual precipitation was about 580 mm, and mean annual streamflow 44-81 mm at the two experimental catchments and 102 mm at the larger one. Most streamflow occurred during winter and spring in the three catchments. At Montseny, rainfall was higher, and mean annual streamflow was 495 mm in the experimental catchment, and 760 mm in the larger catchment, though these data were obtained in different periods in each catchment. Streamflow was roughly equal in autumn, winter and spring. At both sites flow duration curves were fairly similar in the small experimental catchments and the larger catchments. The higher streamflow at Montseny is reflected in its flow duration curves being well above those at Prades. The experimental catchments at Prades are thus fairly representative of the investigated hydrological characteristics. At Montseny, hydrological differences between the experimental catchment and the larger catchment are probably due to the higher mean altitude of the latter and to the non-overlapping periods of their streamflow records.
Keywords: EXPERIMENTAL CATCHMENT; montseny; prades; QUERCUS-ILEX; STREAMFLOW; Water budget

Structure, biomass and production of a resprouted holm-oak (Quercus ilex L.) forest in NE Spain - LLEDO, M J; Sánchez, J R; Bellot, J; Boronat, J (Plant Ecology, 1992)
When considered as a compartment of nutrients (biomass) and as a flux between compartments (pro- duction) vegetation plays an important role in the biogeochemical forest research that is carried out at the Prades research station in two adjacent catchments: L'Avic (51.6 ha) and La Teula (38.5 ha). The forest density at the Prades site, considering both the tree and shrub layers, is 9182 stems ha t, with 4527 stems ha i being the tree layer. The predominant species is Quercus ilex with Arbutus unedo and Phillyrea media less common. The structure of the population, estimated by grouping the numbers of the stems in classes of 2.5 cm, shows a distribution which conforms, in both catchments, to a negative exponential equation following the Yoda law. The distribution observed at different altitudes shows great heterogeneity, the number of stems of Q. ilex increases with altitude, from 4000 stems ha ~ at 800 m, to 14000 stems ha 1 at 1000 m of altitude. The upper and the lower parts of the watershed show dif- ferences in forest production that explain this variation. In this paper the influence of human activities and physical factors on the origin of this structure is discussed. The tree and shrub biomass was cal- culated by applying allometric regressions for the three predominant species and has been estimated as 113.2 t ha 1. The tree layer accounts for 92°o. Net production was calculated from annual increases (by differences between the 1981 and 1986 basal area measures) of the woody part and the litterfall. The above-ground net production was about 6.5 t ha 1 year 1, 95.4o0 of it being from trees and shrubs and only 4.6°0 from grasses.
Keywords: Forest structure; human activities; mediterranean forest; prades; Species distribution